Internalisasi Tauhid Uluhiyah dalam Pembentukan Karakter Religius Santri: Studi Kasus di Pesantren Rumah Bahasa Arab, Makassar - Andi Mursyid B. Asapa; Rano Sukmantara (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the internalization of tawhid uluhiyah in the formation of students’ religious character at Rumah Bahasa Arab Islamic Boarding School, Makassar. This study aims to analyze the process of value internalization, the role of Islamic boarding school (pesantren), and its impact on students’ religious character. This research uses a qualitative case study approach. Data were collected through observation, interviews, and documentation involving teachers, caregivers, and students. The findings show that the internalization of tawhid uluhiyah is carried out through a structured learning system based on classical tawhid texts taught sequentially, combined with habituation of worship practices, contextual explanation of contemporary deviant beliefs, and continuous supervision. A distinctive finding is the integration of doctrinal learning with real-life case analysis, which helps students critically distinguish between correct and deviant beliefs. This process contributes to the development of sincerity in worship, increased awareness of shirk-related practices, and more disciplined religious behavior. These findings highlight that value internalization in pesantren is most effective when doctrinal understanding is directly connected to students lived experiences.